Gender differences in spinal morphological attributes among young adults: a preliminary study - Devinder Kaur Ajit Singh,; Lim, Ai Yin; Deepashini Harithasan,; Nor Najwatul Akmal Ab Rahman,; Norhafidzah Mohamed Sharif,; Bala S. Rajaratnam, (Penerbit Universiti Kebangsaan Malaysia, 2018)
There is limited information regarding gender differences in spinal morphological attributes among healthy young adults although alterations have been reported to influence postural changes, mainly with forward-bending and extension postures. The aim of this preliminary study was to examine gender differences in spinal morphological attributes of lumbar extensor muscles that includes its muscle fibre angles, thickness, endurance and thoracolumbar curvature among young adults. Nineteen male and 26 female healthy young adults (aged 21-24 years) matched for age, body mass index and physical activity levels participated in this preliminary study. Fibre angles and thickness of lumbar extensor muscles were examined using ultrasonography. Lumbar extensor muscle endurance and thoracolumbar curvatures were assessed using Sorenson’s test and a flexible ruler respectively. Paired t-test showed a significant mean difference (p < 0.01) between the right and left fibre angles. However, no significant mean difference (p = 0.50) was found between the right and left muscle thickness. Results of independent t-test showed a significant difference (p < 0.01) in muscle thickness between males and females. No significant differences were shown in right fibre angle (p = 0.12), left fibre angle (p = 0.89), muscle endurance (p = 0.46), thoracic curvature (p = 0.76) and lumbar curvature (p = 0.06) between genders. There were no gender differences in spinal morphological attributes except for lumbar extensor muscle thickness in young adults age between 21 to 24. This study data may be useful as an initial reference norm of spinal morphological attributes among young adults. Further studies may be required to examine the factors that may influence changes in spinal morphological attributes among healthy adults.